Representation of ideological conflict in the j. r. r. tolkien's trilogy the lord of the rings novel (1937 - 1949) - Nugrahawati, Ana Wiyasa; , Prof. Dr. C. Bakdi Sumanto; , Dr. M. Thoyibi, M.S (2014)
There are a lot of ideologies in the J. R. R. Tolkiens Trilogy The Lord of The Rings novel. From those ideologies there are shared ideology and conflict ideology. In the writing this research paper, the writer focuses on the ideological conflict. The theories are used in this research paper are ideology, conflict theory and representation. Sociological approaches and context oriented approach are support theories to analyze the representation of ideological conflict. The main objective of this research is to analyze the ideological conflict reflected in The Lord Of The Rings novel (1937 - 1949). The question to be discussed are how is the ideological conflict are reflected in the the J. R. R. Tolkiens Trilogy The Lord of The Rings novel (1937 - 1949) The research is used is the qualitative research. The object of this research is the The Lord Of The Rings novel. This novel is written by John Ronald Reuel Tolkien at 1937 - 1949. The subject of this study is the representation of ideological conflict. The procedure in the collecting data is taking note from primary sources (The Lord of The Rings) and the secondary sources (journal, books and article). In the checking of data validation, the writer used the triangulation technique. The procedures of analysis are reading the novel, elaborate the elements of ideologies, and elaborate the ideological conflict. The general finding is the beliefs from the ideology and the form of domination by the government in the society are influencing the ideological conflict. The specific findings are the shared and conflict ideology, the cause and effect of ideological conflict, the representation of ideology and ideological conflict. In the discussing of finding, the writer used the context oriented approach especially in the discussing the representation of ideology and ideological conflict. The context is the condition of society at the time when the novel is written. So that, the writer used the sociological approach to investigate the condition of society in the writing of novel.